"Dollars and Listeners": Revisiting the Great New Zealand Radio Experiment of Market Deregulation. Issue 1 (2nd January 2021) - McEwan, Rufus; Mollgaard, Matt
ABSTRACT: During the 1980s New Zealand embarked on a neoliberal project to deregulate as much of the economy as possible. This deregulation included media systems, with radio broadcasting one of the most thoroughly reformed sectors. Critiques of these significant changes and their wide-reaching outcomes were articulated by scholars and pundits from early in the process, reaching a zenith in 2005 with the publication of a book focused on the impact of the deregulation of New Zealand radio titled The Great New Zealand Radio Experiment. This article accepts a key challenge from this volume to interrogate the deregulated commercial radio market in terms of delivering both "dollars and listeners" in years to come. Thirty years on from deregulation and 15 years since this key critical publication, we find that commercial radio in New Zealand has managed to both keep significant listenership and to hold its share of advertising revenue, despite the misgivings of earlier scholarship. This article revisits the deregulation debate and examines the strategies that commercial radio has used to remain relevant to audiences and advertisers and to survive and thrive in the digital age.